Ways of examining speech acts in young african american children: considering inside-out and outside-in approaches. - Dejarnette, Glenda; Rivers, Kenyatta O; Hyter, Yvette D (Topics in Language Disorders, 2015)
To develop a framework for further study of pragmatic behavior in young children from African American English (AAE) speaking backgrounds, one aspect of pragmatic behavior is explored in this article, specifically, speech acts. The aims of this article are to (1) examine examples of how external taxonomies (i.e., an “etic” or “outside-in” approach) have been applied to the speech act behavior of AAE child speakers and to note that etic approaches alone do not identify cultural characteristics that influence the presentation of speech acts in this population; (2) conceptualize a culture-sensitive framework where components of AAE speech act behaviors can be identified as gleaned from existing linguistic research; and (3) explain the utility of analyses of speech act behavior using taxonomies that have emerged from the cultural language style of AAE speakers, that is, an “emic” or “inside-out” approach.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-681-907-287-000 tex.type: [object Object]
Keywords: English speakers; communicative functions; dept.cmd; language behavior; pragmatic behavior; speech acts; young African American

Pragmatic language of african american children and adolescents: A systematic synthesis of the literature. - Hyter, Yvette D; Rivers, Kenyatta O; Dejarnette, Glenda (Topics in Language Disorders, 2015)
Purpose: A systematic review and synthesis was performed on published articles and dissertations produced between 1970 and 2013 that focused on selected pragmatic language behaviors of African American children and adolescents. Methods: Electronic databases and hand searches of articles located in the databases were used to identify the published articles and dissertations. Each article or dissertation was reviewed by at least 2 of the authors to determine whether it met the criteria for inclusion in this study. Selected observations of the documents that met criteria for inclusion were recorded on the Primary Research Appraisal Tool (PRAT; DeJarnette, Hyter, & Rivers, 2012), a data gathering and analysis framework developed by the authors specifically for this systematic synthesis. Results: The literature search resulted in 92 research articles and dissertations, 37 of which were eliminated because they did not meet all of the inclusion criteria. The documents that met our inclusion criteria focused primarily on the structure and/or content of narrative discourse rather than speech acts, other forms of discourse (e.g., conversation, expository), and presupposition/perspective taking skills. Six major themes identified in the major findings are used to summarize studies reviewed for this systematic synthesis. Conclusions: We (a) explain the current state of knowledge about African American pragmatic language behaviors, (b) explain major findings and implications of the extant literature in this topical area and how it may inform speech-language pathology practice, and (c) identify directions for future research on pragmatic language of African American children and adolescents.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/151-173-234-950-684 tex.type: [object Object]
Keywords: African American; communication functions; dept.cmd; discourse; pragmatic language; presupposition; speech acts; systematic review and synthesis; theory of mind